Medidas invasivas realizadas em pacientes com câncer avançado em cuidados paliativos em terapia intensiva - CARMO, Reivax Silva do (2024)
Introduction: Introduction: Cancer represents a serious public health problem in Brazil, where more than half of patients are diagnosed at an advanced stage of the disease. The rationalization of therapeutic measures must take pride of place in the follow-up of these patients, since prolonging the process of death that has already begun can generate unnecessary suffering. The objective of this study is to evaluate invasive interventions performed on patients with advanced cancer admitted to the ICU. Methodology: Observational, cross-sectional study, with a quantitative approach, carried out with patients with advanced cancer and admitted to ICUs of oncology hospitals, in the State of Maranhão. The Supportive And Palliative Care Indicators (SPCIT) scales were used to evaluate the indication for PC, Eastern Cooperative Oncologic Group/Karnofsky Performance (ECOG/KPS) and Charlson Comorbidity Index (CCI) to evaluate severity, description of procedures invasive procedures carried out and application of the surprise question. The association between the data obtained was tested using the chi-square test, logistic regression, Poisson regression and survival curve. Results: The main characteristics found in this sample were: the majority of adults/elderly, gynecological cancer (22.7%), gastrointestinal tract (22.7%) and breast (13.8%), with metastasis (90.0% ), palliative chemotherapy (65.3%), positive SPICT (99.0%), severe with KPS/ECOG score 4 (61.0%) and ICC score 6 (93.0%), with 85, 0% “No” response to the surprise question and association of significance with the death outcome, in addition to being without PC monitoring (96.0%) and without directives of wishes (99.0%). Indwelling urinary catheter (SVD), central venous access (CVC), mechanical ventilation (MV) and vasoactive drug (VAD) were the most commonly performed invasive procedures, with SVD as a protective factor and odds ratio (OR) of 0.23 and MV as a risk factor and OR of 3.39 for death. In the Poisson regression, MV presented a prevalence ratio (PR) of 197.0% and DVA of 162.0% for the outcome death. The average hospitalization of patients was 10.3 days and 54.5% died. Conclusions: It is concluded that patients with advanced, metastatic cancer, with eligibility criteria for PC, considered serious, were referred to the ICU and underwent invasive procedures such as SVD, CVC, DVA, MV and even so, 54.5% died within a few days of hospitalization. In addition, no evaluation/monitoring was requested by the CP team.